Nudges at the dentist - Steffen Altmann; Christian Traxler (Institute for the Study of Labor (IZA), 2012)
We implement a randomized field experiment to study the impact of reminders on dental health prevention. Patients who are due for a check-up receive no reminder, a neutral reminder postcard, or reminders including additional information on the benefits of prevention. Our results document a strong impact of reminders. Within one month after receiving a reminder, the fraction of patients who make a check-up appointment more than doubles. The effect declines slightly over time, but remains economically and statistically significant. Including additional information in the reminders does not increase response rates. In fact, the neutral reminder has the strongest impact for the overall population as well as for important subgroups of patients. Finally, we document that being exposed to reminders repeatedly does neither strengthen nor weaken their effectiveness.
Keywords: D03; I11; C93; 330; field experiment; reminders; nudges; memory limitations; prevention; dental health; framing; Zahnarztpraxis; Gesundheitsvorsorge